Novel radioligands for imaging sigma-1 receptor in brain using positron emission tomography (PET) - Yu Lan; Ping Bai; Zude Chen; Ramesh Neelamegam; Michael S. Placzek; Hao Wang; Stephanie A. Fiedler; Jing Yang; Gengyang Yuan; Xiying Qu; Hayden R. Schmidt; Jinchun Song; et al. (Elsevier, 2019)
The sigma-1 receptor (σ1R) is a unique intracellular protein. σ1R plays a major role in various pathological conditions in the central nervous system (CNS), implicated in several neuropsychiatric disorders. Imaging of σ1R in the brain using positron emission tomography (PET) could serve as a noninvasively tool for enhancing the understanding of the disease's pathophysiology. Moreover, σ1R PET tracers can be used for target validation and quantification in diagnosis. Herein, we describe the radiosynthesis, in vivo PET/CT imaging of novel σ1R 11C-labeled radioligands based on 6-hydroxypyridazinone, [11C]HCC0923 and [11C]HCC0929. Two radioligands have high affinities to σ1R, with good selectivity. In mice PET/CT imaging, both radioligands showed appropriate kinetics and distributions. Additionally, the specific interactions of two radioligands were reduced by compounds 13 and 15 (self-blocking). Of the two, [11C]HCC0929 was further investigated in positive ligands blocking studies, using classic σ1R agonist SA 4503 and σ1R antagonist PD 144418. Both σ1R ligands could extensively decreased the uptake of [11C]HCC0929 in mice brain. Besides, the biodistribution of major brain regions and organs of mice were determined in vivo. These studies demonstrated that two radioligands, especially [11C]HCC0929, possessed ideal imaging properties and might be valuable tools for non-invasive quantification of σ1R in brain. KEY WORDS: σ1R, PET, Brain imaging, 6-Hydroxypyridazinone, 11C-labeled radioligand